Рассказы - Житков Борис Степанович (Школьная библиотека, 2017)
Экземпляры: ф.21 (20220221) / Инвентарный номер: 61817 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ж 74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44